Review of factors driving student achievement: the context of the Mechanics of Civil Engineering Structure Course at Sultan Mizan Zainal Abidin Polytechnic - Ab Ghani, Rosmida (Jurnal Penyelidikan Sains Sosial, 2025)
The mastery of the DCC 20053- Mechanics of Civil Engineering Structure course is closely related to mathematics and additional mathematics subjects in school. The course covers the knowledge, basic principles of force, material strength that requires problem-solving techniques using additional mathematical and mathematical skills. The course is considered difficult, complicated and many concepts to understand for some students who have a weak mathematical foundation and do not take extra math while in school. This presents a high challenge for students to master the course. Mastery of a course is closely linked to academic excellence, which significantly influences student achievement. Hence, this study was conducted to identify the key factors affecting student performance in the Mechanics of Civil Engineering Structure course at the Civil Engineering Department (JKA), Sultan Mizan Zainal Abidin Polytechnic (PSMZA). A questionnaire was administered to 99 students enrolled in this course during Session II 2023/2024 and Session I 2024/2025. The data collected was analyzed using descriptive statistics, T-Test, and Pearson Correlation through the Statistical Package for Social Sciences (SPSS) software, version 22. The results indicated that the 'lecturer' was the most influential factor in student performance, achieving the highest mean score of 4.76, surpassing other factors such as prior knowledge, interests, attitudes, peers, and environment. The T-Test analysis revealed no significant difference between attitude and gender, with a value of (t = 1.07) and p > 0.05 (0.29). Similarly, Pearson’s correlation analysis identified a modest yet significant relationship between 'peers' and interests. These findings provide valuable insights into the factors influencing student achievement in the Mechanics of Civil Engineering Structure course at JKA, PSMZA. Furthermore, the study's outcomes can assist JKA in implementing Continuous Quality Improvement (CQI) initiatives to enhance student performance across all aspects of the course.